Modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

By immersing and high-temperature annealing of the lithium-rich manganese-based positive electrode material, fluorine doping improves surface stability, solving the problems of material circulation stability and specific capacity, and achieving high-performance lithium-ion battery positive electrode material.

CN119230815AActive Publication Date: 2024-12-31SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411526745.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-31
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have severe surface oxygen loss during the circulation process, resulting in poor circulation stability, and commonly used surface treatment methods will reduce the specific capacity of the material.

Method used

The lithium-rich manganese-based positive electrode material is impregnated and high-temperature annealed by fluorocarbon surfactant. The surface stability of the material is improved by fluorine doping, and a modified lithium-rich manganese-based positive electrode material is formed.

Benefits of technology

It significantly improves the cycle stability and discharge specific capacity of the material, maintains a high theoretical specific capacity, and is suitable for large-scale commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230815A_ABST
    Figure CN119230815A_ABST
Patent Text Reader

Abstract

The invention provides a modified lithium-rich manganese-based positive electrode material as well as a preparation method and application thereof, and the preparation method of the modified lithium-rich manganese-based positive electrode material comprises the following steps: dipping the lithium-rich manganese-based positive electrode material by using a fluorocarbon surfactant, and performing high-temperature annealing to obtain the modified lithium-rich manganese-based positive electrode material, the modified lithium-rich manganese-based positive electrode material is prepared by the preparation method of the modified lithium-rich manganese-based positive electrode material, and is applied to the field of lithium ion batteries. Compared with the prior art, the modified lithium-rich manganese-based positive electrode material has the advantages that the relatively high theoretical specific capacity of the lithium-rich manganese-based positive electrode material is reserved, the surface stability of the material is improved through fluorine doping of crystal lattices on the surface of the material, and the modified lithium-rich manganese-based positive electrode material which is excellent in rate capability and more stable in long-term cycle performance and is applied to the field of lithium ion batteries is formed; the preparation method is simple in process and high in operability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art

[0002] As a new type of environmentally friendly energy storage device, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage since their commercialization in the 1990s. Although LiCoO2 and LiFePO4 have been successfully commercialized on a large scale in the past decade, they still have many problems that need to be solved. For example, LiCoO2 is structurally unstable after delithiation and is prone to side reactions with the electrolyte, resulting in irreversible capacity loss and safety issues. In addition, their low available capacity (theoretical capacity <200 mAh / g) can no longer meet people's demand for longer battery life in electric vehicles. Therefore, the development of a high-capacity, long-life, high-stability, high-safety, and low-cost lithium-ion battery cathode material has become the key to breaking through the bottleneck of energy development.

[0003] Among the common material systems, layered oxide cathode materials have attracted widespread attention due to their high theoretical capacity. Among them, lithium-rich manganese-based layered cathode materials have a theoretical specific capacity of up to 250 mAh / g and are considered to be highly promising next-generation high-performance lithium-ion battery cathode materials. Its chemical formula can be expressed as xLi2MnO3·(1-x)LiMO2. Usually, according to the two-phase structure theory, we believe that it is composed of layered Li2MnO3 and LiMO2 (M= Ni, Co, Mn), in which one-third of the Li in the Li2MnO3 phase is Li + Mn 4+ Replacement forms a monoclinic crystal with a space group of C / 2m, while LiMO2 is similar to the layered structure of lithium cobalt oxide with a space group of R-3m. This unique two-phase chelated structure allows the transition metal ions and oxygen anions in the lithium-rich manganese-based positive electrode material to participate in the electrochemical reaction, so that it has a higher theoretical specific capacity than the traditional ternary material. At present, in order to achieve large-scale commercialization of lithium-rich manganese-based positive electrode materials, the key scientific problem to be solved is how to better stabilize the lattice oxygen and reduce the surface oxygen loss of the material during the cycle to improve the long-term cycle stability of the material. At present, surface treatment, surface coating and anion and cation doping are mostly used to enhance the stability of the material, but these methods often lead to a decrease in the specific capacity of the material due to the introduction of electrochemically inert components. Therefore, finding a modification method that can not only improve the cycle stability of lithium-rich manganese-based positive electrode materials without affecting their actual discharge specific capacity is a key problem that needs to be solved urgently. Summary of the invention

[0004] In view of the defects in the prior art, the purpose of the present invention is to provide a modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof, which not only retains the high theoretical specific capacity of the lithium-rich manganese-based positive electrode material itself, but also improves the surface stability of the material by fluorine doping the surface lattice of the material, thereby forming a modified lithium-rich manganese-based positive electrode material for use in the field of lithium-ion batteries with excellent rate performance and more stable long-term cycle performance.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: According to a first aspect of an embodiment of the present invention, there is provided a method for preparing a modified lithium-rich manganese-based positive electrode material, comprising the following steps: The modified lithium-rich manganese-based positive electrode material is obtained by impregnating the lithium-rich manganese-based positive electrode material with a fluorocarbon surfactant and annealing at a high temperature.

[0006] In a further preferred embodiment, the fluorocarbon surfactant is at least one of perfluorooctane sulfonic acid, perfluorooctanoic acid, perfluorobutyl sulfonic acid, perfluorooctylethanol, perfluorohexyl sulfonic acid, perfluorohexanoic acid or perfluorodecane sulfonic acid.

[0007] In a further preferred embodiment, the preparation method specifically comprises the following steps: Step 1, uniformly dispersing the powder of the lithium-rich manganese-based positive electrode material in an aqueous solution containing the fluorocarbon surfactant, and then immersing it at room temperature, wherein the concentration of the fluorocarbon surfactant aqueous solution used is 0.5-50%, and the immersion time is 2-24 h. After the immersion is completed, the powder is separated and dried to obtain a lithium-rich manganese-based positive electrode material with the fluorocarbon surfactant adsorbed on the surface; Step 2: Evenly mix the powder of the lithium-rich manganese-based positive electrode material with the carbon-fluorine surfactant adsorbed on the surface with a certain amount of lithium hydroxide monohydrate or lithium carbonate in a mortar, and then calcine at high temperature to obtain the modified lithium-rich manganese-based positive electrode material.

[0008] In a further preferred embodiment, the fluorine content of the modified lithium-rich manganese-based positive electrode material in step 2 is between 0.1% and 10%.

[0009] In a further preferred embodiment, the amount of the lithium hydroxide monohydrate or the lithium carbonate added in step 2 is 0.1-5 wt%.

[0010] In a further preferred embodiment, the high temperature calcination in step 2 is carried out by a one-step sintering method at 600-900 o C in an oxygen or air atmosphere for 1-10 h.

[0011] In a further preferred embodiment, the powder is separated and dried after the impregnation in step 2 to obtain a lithium-rich manganese-based positive electrode material with a fluorocarbon surfactant adsorbed on the surface, which specifically includes: After the impregnation, the powder was separated by centrifugation and heated at 80-120 o C, and drying the powder to obtain a lithium-rich manganese-based positive electrode material with a carbon-fluorine surfactant adsorbed on the surface.

[0012] In a further preferred embodiment, the lithium-rich manganese-based positive electrode material in the preparation method of the modified lithium-rich manganese-based positive electrode material described in any one of the above is a cobalt-free Li 1.2 Ni 0.2 Mn 0.6 O2 or Li containing cobalt 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 At least one of .

[0013] According to a second aspect of an embodiment of the present invention, a modified lithium-rich manganese-based positive electrode material is provided, which is prepared by any one of the above-mentioned methods for preparing a modified lithium-rich manganese-based positive electrode material.

[0014] According to a third aspect of an embodiment of the present invention, an application of a modified lithium-rich manganese-based positive electrode material is provided. The modified lithium-rich manganese-based positive electrode material is prepared by any of the above-mentioned preparation methods for the modified lithium-rich manganese-based positive electrode material and is applied in the field of lithium-ion batteries.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with the untreated material, the cycle stability of the doped material is significantly improved. Fluoride ions are doped in the surface lattice of the modified lithium-rich manganese-based cathode material. Since the strength of the TM-F bond is higher than that of the TM-O bond, the surface transition metal of the modified material dissolves less during the cycle. Therefore, surface F doping can reduce the dissolution of transition metals in the lithium-rich manganese-based cathode material during the cycle.

[0016] (2) The introduction of fluorine is beneficial to stabilizing the oxygen skeleton on the surface of the material, improving the stability of the lattice oxygen on the surface of the lithium-rich manganese-based positive electrode material, reducing the irreversible oxygen loss during the cycle when the material is charged to a high voltage, and thus improving the long-term cycle stability of the material.

[0017] (3) Since this trace amount of surface doping does not introduce too many electrochemically inert components, the resulting modified lithium-rich manganese-based positive electrode material still has a high discharge specific capacity and is more suitable for large-scale commercial applications.

[0018] (4) The method of impregnation with an aqueous solution of a fluorocarbon surfactant combined with high-temperature calcination is simple to implement and is conducive to commercialization.

[0019] In summary, the present invention not only retains the high theoretical specific capacity of the lithium-rich manganese-based positive electrode material itself, but also improves the surface stability of the material by fluorine doping the surface lattice of the material, thereby forming a modified lithium-rich manganese-based positive electrode material for lithium-ion batteries with excellent rate performance and more stable long-term cycle performance. The preparation method provided by the present invention is simple in process and highly operable. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 The lithium-rich manganese-based positive electrode material Li before and after modification provided in the embodiment of the present invention 1.2 Ni 0.13 Co 0.13 Mn 0.54 X-ray diffraction spectrum of O2; Figure 2 The lithium-rich manganese-based positive electrode material Li before modification provided in the embodiment of the present invention 1.2 Ni 0.13 Co 0.13 Mn 0.54 SEM spectrum of O2; Figure 3 The modified lithium-rich manganese-based positive electrode material Li provided in the embodiment of the present invention 1.2 Ni 0.13 Co 0.13 Mn 0.54 SEM spectrum of O2; Figure 4 The lithium-rich positive electrode material Li before and after modification provided in the embodiment of the present invention 1.2 Ni 0.13 Co 0.13 Mn 0.54 XPS full spectrum of O2; Figure 5 The lithium-rich positive electrode material Li provided in the embodiment of the present invention 1.2 Ni 0.13 Co 0.13 Mn 0.54 Electrochemical test discharge data of O2 as the positive electrode material at 1 C rate (1C = 250 mAh / g) (the battery was formed at 0.1 C rate in the first cycle); Figure 6 The lithium-rich positive electrode material Li before modification provided in the embodiment of the present invention 1.2 Ni 0.13 Co0.13 Mn 0.54 Cyclic voltammogram of O2; Figure 7 The modified lithium-rich positive electrode material Li provided in the embodiment of the present invention 1.2 Ni 0.13 Co 0.13 Mn 0.54 Cyclic voltammogram of O2; Figure 8 The lithium-rich positive electrode material Li before and after modification provided in the embodiment of the present invention 1.2 Ni 0.13 Co 0.13 Mn 0.54 Impedance diagram of O2 after 50 cycles at 2C rate. DETAILED DESCRIPTION

[0021] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0022] The unique properties of fluorocarbon surfactants are directly related to the fluorocarbon chain, and further, they depend on the unique properties of the fluorine element. Fluorine is the most electronegative element, with high oxidation potential and high ionization energy. This property causes the fluorine-carbon bond (F-C) to have high bond energy (in fact, the fluorine-carbon bond is the covalent bond with the highest known bond energy). Fluorocarbon surfactant molecules have a stronger tendency to leave the aqueous solution than other surfactant molecules in the aqueous solution, and are oriented to aggregate and arrange into molecular films at the liquid / gas interface, so that they have two properties different from other surfactants. Utilizing these properties of fluorocarbon surfactants, the present invention proposes that the lithium-rich manganese-based positive electrode material can be impregnated with its aqueous solution, and then centrifuged and dried to obtain a lithium-rich manganese-based positive electrode material covered with a fluorocarbon surfactant molecular film on the surface. Finally, after high-temperature calcination, the fluorine ions contained in the fluorocarbon surfactant diffuse into the lattice on the surface of the lithium-rich manganese-based positive electrode material to replace the oxygen ions on the surface. Since the strength of the TM-F bond is higher than that of the TM-O bond, surface F doping can reduce the dissolution of transition metals in the lithium-rich manganese-based positive electrode material during the cycle. In addition, the introduction of fluorine can also improve the stability of the lattice oxygen on the surface of lithium-rich manganese-based cathode materials, reduce irreversible oxygen loss during the cycle, and thus improve the long-term cycle stability of the material. At the same time, since this trace amount of surface doping does not introduce too many electrochemically inert components, the modified lithium-rich manganese-based cathode material still has a high discharge specific capacity and is more suitable for large-scale commercial applications.

[0023] Embodiment 1: The present invention provides a method for preparing a modified lithium-rich manganese-based positive electrode material, which comprises the following steps: (1) The powder of the lithium-rich manganese-based positive electrode material is evenly dispersed in an aqueous solution containing a carbon fluorine surfactant, and then impregnated at room temperature. After the impregnation, the powder is separated using a centrifuge and fully dried in an oven.

[0024] (2) The impregnated lithium-rich manganese-based positive electrode material powder prepared in step (1) is mixed evenly with a certain amount of lithium hydroxide monohydrate or lithium carbonate in a mortar, and then calcined at a high temperature in a muffle furnace to obtain a modified lithium-rich manganese-based positive electrode material.

[0025] In step (1): The impregnation method is to pour the powder of the lithium-rich manganese-based positive electrode material into an aqueous solution containing a certain concentration of fluorocarbon surfactant and immerse it at room temperature for 2-24 hours. Then, by centrifugation and drying, a lithium-rich manganese-based positive electrode material with fluorocarbon surfactant adsorbed on the surface is obtained. After the impregnation is completed, the powder is separated by centrifugation and heated at 80-120 o C, the lithium-rich manganese-based positive electrode material powder with a carbon-fluorine surfactant adsorbed on the surface is fully dried in an oven.

[0026] In step (2): High temperature calcination is to mix the lithium-rich manganese-based cathode material powder with a carbon-fluorine surfactant adsorbed on the surface with a certain amount of lithium carbonate or lithium hydroxide monohydrate in a mortar, and then heat it in a muffle furnace at 600-900 o C for 1-10 h to obtain a modified lithium-rich manganese-based positive electrode material.

[0027] In a specific embodiment, the modified lithium-rich manganese-based positive electrode material is prepared by the following steps: The first step is to add 2 g of lithium-rich cathode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 was added to 50 mL of 0.5 mol% perfluorooctanoic acid aqueous solution, the solution was stirred at room temperature for 4 h, and then the mixed solution was transferred to a centrifuge tube, and the powder was separated by centrifuge and then placed at 80 o C oven for 12 h.

[0028] In the second step, 1 g of the treated lithium-rich cathode material powder obtained in the first step was weighed and mixed evenly with 0.01 g of lithium carbonate in a mortar. After that, the mixed powder was transferred to a box-type muffle furnace and heat-treated at 800 °C for 4 h to obtain the modified lithium-rich cathode material target product.

[0029] See also Figure 1-4 , which are respectively the lithium-rich manganese-based materials Li and Li and before and after modification prepared in this embodiment. 1.2 Ni 0.13 Co 0.13 Mn 0.54 X-ray diffraction spectrum, scanning electron microscope spectrum, and transmission electron microscope spectrum of O2. From the X-ray spectrum, it can be seen that the diffraction peaks of the materials before and after modification are consistent with the characteristics of lithium-rich layered positive electrode materials. The diffraction peaks correspond well to the R-3m and C / 2m space groups. The (003) peak of the material is significantly higher than the (104) peak, indicating that the degree of Li / Ni ion mixing is low, and the peak separation of the (018) peak and the (110) peak is relatively obvious, which shows that the materials before and after modification have a good layered structure. Figure 4 The XPS spectrum in the figure shows that the signal of F element is increased in the modified lithium-rich material, which indicates that F is successfully introduced into the surface of the material. Figure 2 and Figure 3 The scanning electron microscope spectrum also shows that the use of a fluorocarbon surfactant aqueous solution to impregnate the lithium-rich material and subsequent high-temperature treatment will not damage the material's morphology, and it can still maintain a micron-sphere-like morphology, which is beneficial to improving the material's compaction density.

[0030] Embodiment 2: Different from Example 1, the modified lithium-rich manganese-based positive electrode material in this example is prepared by the following steps: The first step is to add 2 g of lithium-rich cathode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 was added to 50 mL of an aqueous solution containing 1 mol% perfluorobutanesulfonic acid, and the solution was stirred at room temperature for 6 h. The mixed solution was then transferred to a centrifuge tube, and the powder was separated using a centrifuge and then dried in an oven at 120 oC for 12 h.

[0031] Step 2: Weigh 1 g of the treated lithium-rich cathode material powder obtained in step 1 and mix it with 0.03 g of lithium carbonate in a mortar. Then, transfer the mixed powder to a box-type muffle furnace and heat it at 750 °C. o C for 4 h to obtain the target product of modified lithium-rich cathode material.

[0032] Embodiment 3: Different from Example 1, the modified lithium-rich manganese-based positive electrode material in this example is prepared by the following steps: The first step is to add 2 g of lithium-rich cathode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 was added to 50 mL of an aqueous solution containing 2 mol% heptafluorobutyric acid. The solution was stirred at room temperature for 6 h. The mixed solution was then transferred to a centrifuge tube and the powder was separated using a centrifuge. The powder was then placed at 80 o C oven for 12 h.

[0033] Step 2: Weigh 1 g of the treated lithium-rich cathode material powder obtained in step 1 and mix it with 0.02 g of lithium hydroxide monohydrate in a mortar. Then, transfer the mixed powder to a box-type muffle furnace and heat it at 850 °C. o C for 6 h to obtain the target product of modified lithium-rich positive electrode material.

[0034] Example 4: Different from Example 1, the modified lithium-rich manganese-based positive electrode material in this example is prepared by the following steps: The first step is to add 2 g of lithium-rich cathode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 was added to 50 mL of 1 mol% perfluorohexanoic acid aqueous solution and the solution was heated at 50 o The mixture was stirred in a water bath at 80 °C for 4 h, and then the mixed solution was transferred to a centrifuge tube, and the powder was separated by a centrifuge and then dried in an oven at 80 °C for 12 h.

[0035] Step 2: Weigh 1 g of the treated lithium-rich cathode material powder obtained in step 1 and mix it with 0.02 g of lithium hydroxide monohydrate in a mortar. Then, transfer the mixed powder to a box-type muffle furnace and heat it at 800 °C. o C for 2 h to obtain the target product of modified lithium-rich cathode material.

[0036] Embodiment 5: Different from Example 1, the modified lithium-rich manganese-based positive electrode material in this example is prepared by the following steps: The first step is to add 2 g of lithium-rich cathode material Li 1.2 Ni 0.2 Mn 0.6 O2 was added to 50 mL of 1 mol% perfluorohexanoic acid aqueous solution and the solution was heated at 50 oThe mixture was stirred in a water bath at 80 °C for 6 h, and then the mixed solution was transferred to a centrifuge tube, and the powder was separated by a centrifuge and then dried in an oven at 80 °C for 12 h.

[0037] Step 2: Weigh 1 g of the treated lithium-rich cathode material powder obtained in step 1 and mix it with 0.02 g of lithium carbonate in a mortar. Then, transfer the mixed powder to a box-type muffle furnace and heat it at 600 °C. o C for 6 h to obtain the target product of modified lithium-rich positive electrode material.

[0038] Embodiment 6: Different from Example 1, the modified lithium-rich manganese-based positive electrode material in this example is prepared by the following steps: The first step is to add 2 g of lithium-rich cathode material Li 1.2 Ni 0.2 Mn 0.6 O2 was added to 50 mL of an aqueous solution containing 2 mol% perfluorodecyl sulfonic acid. The solution was stirred at room temperature for 12 h. The mixed solution was then transferred to a centrifuge tube and the powder was separated using a centrifuge. The powder was then placed at 80 o C oven for 12 h.

[0039] Step 2: Weigh 1 g of the treated lithium-rich cathode material powder obtained in step 1 and mix it with 0.02 g of lithium hydroxide in a mortar. Then, transfer the mixed powder to a box-type muffle furnace and heat it at 900 °C. o C for 1 h to obtain the target product of modified lithium-rich cathode material.

[0040] Embodiment 7: Different from Example 1, the modified lithium-rich manganese-based positive electrode material in this example is prepared by the following steps: The first step is to add 2 g of lithium-rich cathode material Li 1.2 Ni 0.2 Mn 0.6 O2 was added to 50 mL of 3 mol% perfluorooctanoic acid aqueous solution, the solution was stirred at room temperature for 6 h, and then the mixed solution was transferred to a centrifuge tube, and the powder was separated by centrifuge and then placed at 120 o C oven for 12 h.

[0041] Step 2: Weigh 1 g of the treated lithium-rich cathode material powder obtained in step 1 and mix it with 0.05 g of lithium hydroxide monohydrate in a mortar. Then, transfer the mixed powder to a box-type muffle furnace and heat it at 800 °C. oC, heat treated in an oxygen atmosphere for 2 h to obtain the target product of modified lithium-rich positive electrode material.

[0042] Embodiment 8: This embodiment illustrates the lithium-rich manganese-based material Li before and after modification provided by the present invention. 1.2 Ni 0.13 Co 0.13 Mn 0.54 After O2 is prepared into a battery, the battery performance is tested.

[0043] Electrochemical performance test: (1) Preparation of batteries Before the electrochemical performance test, the sample needs to be made into a button-type lithium battery. The sample serves as the positive electrode material of the electrode in the lithium battery, and the lithium sheet is used as the negative electrode. The production process is pretreatment, slurry preparation, electrode preparation, and battery assembly. The synthesized W-doped lithium-rich layered positive electrode material (80%) is mixed with the conductive agent Super-P (10%) and the binder polyvinylidene fluoride (10%) (mass ratio), NMP is added to fully grind, and then evenly coated on aluminum foil, and then placed in a vacuum drying oven for 120 o C for 12 h, and after drying, use a cutting machine to make a button battery positive electrode sheet, and use 4-6 atmospheres of pressure to press the electrode sheet. Weigh the weight of the electrode sheet coated with active material, subtract the weight of the blank aluminum foil, and then calculate the weight of the active material in each electrode sheet according to the proportion of the active material, and put the weighed electrode sheet into an argon glove box.

[0044] A metal lithium sheet was used as the negative electrode of the battery, and 1 M LiPF6-EC:DMC:EMC = 1:1:1 electrolyte was used. The button cell was assembled in an argon-filled anhydrous and oxygen-free glove box. The battery assembly process was as follows: 1) Place the positive electrode sheet in the middle of the battery shell and use a pipette to drip 1-3 drops of electrolyte; 2) Place the PP diaphragm flatly on the electrode sheet; 3) Use a pipette to drip 1-3 drops of electrolyte in the center of the PP diaphragm to completely wet the diaphragm; 3) Place the metal lithium sheet in the center of the diaphragm, and do not touch the battery shell to avoid battery short circuit; 4) Place the stainless steel gasket and spring sheet on the lithium sheet in turn and align them with the lithium sheet; 5) Cover the negative electrode shell, press it tightly, and use a sealing machine to seal the battery to complete the assembly. The battery was left for 5-12 hours before electrochemical testing.

[0045] (2) Electrochemical performance test The constant current charge-discharge cycle test of the samples was carried out on a LAND-201A battery testing system with a test voltage range of 2.0-4.8 V; the electrochemical impedance spectroscopy test was carried out on a CHIS600B electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.). Figure 5Lithium-rich manganese-based materials before and after modification 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 constant current charge and discharge test diagram, Figure 6 and Figure 7 Lithium-rich manganese-based materials before and after modification 1.2 Ni 0.13 Co 0.13 Mn 0.54 Cyclic voltammetry curve of O2. Figure 5 It can be seen from the constant current charge and discharge test graph that after 1 cycle at 0.1 C rate, after 300 cycles at 1 C rate (1 C = 250 mAh / g), the modified lithium-rich manganese-based positive electrode material has a discharge capacity of 189.74 mAh / g, and a capacity retention rate of 91.7%; while the unmodified lithium-rich manganese-based positive electrode material has a discharge capacity of only 155.97 mAh / g, and a capacity retention rate of only 70.8%, which shows that the modification method of the invention can significantly improve the cycle stability of lithium-rich materials. Figure 6 and Figure 7 From the cyclic voltammetry curve, the electrochemical reversibility of the modified lithium-rich manganese-based positive electrode material is enhanced, which shows that the modification method adopted in the invention is conducive to improving the surface structure stability of the material, thereby alleviating the phase change that may occur when the material is charged to a high voltage. Figure 8 It can be seen from the impedance diagram that after 50 cycles at a large rate of 2 C, the modified lithium-rich positive electrode material has a smaller charge transfer impedance, which indicates that its structure is well maintained after the cycle, explaining its better cycle stability.

[0046] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be arbitrarily combined with each other.

Claims

1. A method for preparing a modified lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: The modified lithium-rich manganese-based positive electrode material is obtained by impregnating the lithium-rich manganese-based positive electrode material with a fluorocarbon surfactant and annealing at a high temperature.

2. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The fluorocarbon surfactant is at least one of perfluorooctane sulfonic acid, perfluorooctanoic acid, perfluorobutyl sulfonic acid, perfluorooctylethanol, perfluorohexyl sulfonic acid, perfluorohexanoic acid or perfluorodecane sulfonic acid.

3. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The preparation method specifically comprises the following steps: Step 1, uniformly dispersing the powder of the lithium-rich manganese-based positive electrode material in an aqueous solution containing the fluorocarbon surfactant, and then immersing it at room temperature, wherein the concentration of the fluorocarbon surfactant aqueous solution used is 0.5-50%, and the immersion time is 2-24 h. After the immersion is completed, the powder is separated and dried to obtain a lithium-rich manganese-based positive electrode material with the fluorocarbon surfactant adsorbed on the surface; Step 2: Evenly mix the powder of the lithium-rich manganese-based positive electrode material with the carbon-fluorine surfactant adsorbed on the surface with a certain amount of lithium hydroxide monohydrate or lithium carbonate in a mortar, and then calcine at high temperature to obtain the modified lithium-rich manganese-based positive electrode material.

4. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The fluorine content of the modified lithium-rich manganese-based positive electrode material in step 2 is between 0.1% and 10%.

5. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: The amount of the lithium hydroxide monohydrate or the lithium carbonate added in the step 2 is 0.1-5 wt %.

6. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The high temperature calcination in step 2 is carried out by a one-step sintering method at 600-900 o C in an oxygen or air atmosphere for 1-10 h.

7. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 6, characterized in that: The step 2 of separating and drying the powder after the impregnation to obtain a lithium-rich manganese-based positive electrode material with a carbon-fluorine surfactant adsorbed on the surface specifically comprises: After the impregnation, the powder was separated by centrifugation and heated at 80-120 o C, and drying the powder to obtain a lithium-rich manganese-based positive electrode material with a carbon-fluorine surfactant adsorbed on the surface.

8. The method for preparing a modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 7, characterized in that: The lithium-rich manganese-based positive electrode material is cobalt-free Li 1.2 Ni 0.2 Mn 0.6 O2 or Li containing cobalt 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 At least one of .

9. A modified lithium-rich manganese-based positive electrode material, characterized in that: The modified lithium-rich manganese-based positive electrode material is prepared by the preparation method according to any one of claims 1 to 8.

10. An application of a modified lithium-rich manganese-based positive electrode material, characterized in that: The modified lithium-rich manganese-based positive electrode material prepared by the preparation method of the modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 8 is applied to the field of lithium-ion batteries.

Citation Information

Patent Citations

  • Fluorocarbon co-doped lithium nickel cobalt manganese oxide positive electrode material and preparation method and application thereof

    CN111430704A

  • Fluorine ion gradient doped lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN114420920A

  • Method for modifying high-nickel positive electrode material by using perfluoro-octanol as well as obtained material and application of modified high-nickel positive electrode material

    CN114927673A

  • Composite oxide containing lithum, nickel, cobalt, manganese, and fluorine, process for producing the same, and lithium secondary cell employing it

    US20060057466A1

Cited By

  • Fluorinated positive electrode material and preparation method and application thereof

    CN121769033A